Functional neuroimaging evidence for distinct neurobiological pathways in Attention-Deficit/Hyperactivity Disorder - Stevens, Michael C. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2017)
BACKGROUND: A challenge facing clinical neuroscientists is how best to synthesize diverse and sometimes inconsistent evidence for neuropsychological deficits and brain system dysfunction found in psychiatric disorders into models that guide etiological and treatment research. Multiple pathway models suggest psychiatric symptoms might arise from pathophysiology in different neural systems. This study tested “dual pathway” model predictions for Attention Deficit Hyperactivity Disorder (ADHD) that reward and executive function cognitive deficits should be related to abnormalities in corresponding functionally-specialized neural systems. METHODS: Behavioral inhibition and preference for immediate rewards were assessed in N=251 adolescent boys and girls ages 12–18 diagnosed with DSM-IV Combined-subtype ADHD or non-ADHD controls. Following taxometric analyses of test performance, the resulting subgroups were compared on an fMRI Monetary Incentive Delay task probing reward anticipation and Go/NoGo task of motor response inhibition. RESULTS: Three ADHD subgroups were identified consistent with different proposed pathways – ADHD with executive function/motor inhibition deficits, ADHD with both executive and reward deficits, and ADHD with relatively normal test performance. Each cognitive domain mapped to different ADHD brain dysfunction features as expected. However, no brain abnormalities were found common to all ADHD subgroups despite the fact they had nearly identical ADHD-related clinical characteristics. CONCLUSIONS: The results suggest Combined-subtype ADHD is a collection of discrete disorders for which a comparable behavioral endpoint arises through different neurobiological pathways. The findings raise caution about applying common cause, single-deficit conceptual models to individual ADHD patients and should prompt researchers to consider biologically-defined, multifactorial etiological models for other psychiatric diagnoses.